ROLE AND PROBLEMS OF DIGITAL TECHNOLOGY IN SMALL BUSINESS AND ENTREPRENEURSHIP - Kosimov Sardor Dilmurodovich (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Digital technology has become an integral part of small businesses and entrepreneurship, revolutionizing the way they operate and compete in today's fast-paced global marketplace. This article explores the role of digital technology in enabling and empowering small businesses while shedding light on the problems and challenges associated with its adoption.